2013
DOI: 10.1016/j.jtcvs.2012.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Patients with type A acute aortic dissection presenting with major brain injury: Should we operate on them?

Abstract: Brain injury at presentation adversely affects hospital survival of patients with type A acute aortic dissection. In the present observational study, the patients selected to undergo surgery demonstrated improved late survival and frequent reversal of neurologic deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 18 publications
3
99
2
Order By: Relevance
“…According to literature, the incidence of brain malperfusion ranges from 7% to 14% (29,30,32,33), and significantly affected the therapeutic management. IRAD data (33) showed that nearly 1 out of 10 TAAD patients are complicated by major brain injury at onset of dissection [cerebrovascular accident (CVA) 4.7%; coma 2.9%], carrying a two or threefold higher mortality depending on presence of CVA or coma respectively. Even in this cohort, surgery was found to be a protective factor against hospital mortality in patients with preoperative brain injury (OR, 0.058; P<0.001), although more than half of these patients do not still undergo TAAD repair.…”
Section: Resultsmentioning
confidence: 99%
“…According to literature, the incidence of brain malperfusion ranges from 7% to 14% (29,30,32,33), and significantly affected the therapeutic management. IRAD data (33) showed that nearly 1 out of 10 TAAD patients are complicated by major brain injury at onset of dissection [cerebrovascular accident (CVA) 4.7%; coma 2.9%], carrying a two or threefold higher mortality depending on presence of CVA or coma respectively. Even in this cohort, surgery was found to be a protective factor against hospital mortality in patients with preoperative brain injury (OR, 0.058; P<0.001), although more than half of these patients do not still undergo TAAD repair.…”
Section: Resultsmentioning
confidence: 99%
“…(16,18). However, when assessing hospital outcomes according to therapeutic management the authors showed that medical therapy was associated with dismal outcomes: 100% mortality in patients with coma and 76.2% in those with cerebrovascular accident (17). However, surgery led to a hospital survival benefit of 49.6% in patients with preoperative neurologic symptoms and 55.6% of those with coma.…”
Section: Resultsmentioning
confidence: 99%
“…Cerebral malperfusion occurs in 6-14% of TAAD patients and results from partial or complete occlusion of the arch vessels by the intimal-medial flap, hypoxic encephalopathy secondary to shock or tamponade and/or brain embolism from thrombus in the false lumen ( Figure 2) (2)(3)(4)14,22). Clinical manifestations of stroke or coma were shown to be predictors for detrimental outcomes, and optimal management of TAAD patients with cerebral malperfusion syndrome remains controversial.…”
Section: Cerebral Malperfusionmentioning
confidence: 99%